AKTIVITAS MEDIA SOSIAL DALAM MEMPROMOSIKAN KAWASAN PARIWISATA DANAU TOBA - Yos Horta Meliala; Muhammad Saifulloh; Eni Kardi Wiyati (Universitas Prof. Dr. Moestopo (Beragama), 2023)
One of the stakeholders in the tourism sector is the Indonesian Tour Guide Association (HPI). Tour guide activities, including communication activities carried out between HPI members in introducing tourism areas. In the digital era and the new normal era, the need to use various communication media such as social media has a very high role. The research objectives are; 1) analyze the influence of social media activities at HPI in promoting the Lake Toba tourism area; 2) analyze the factors that influence the promotion of the Lake Toba tourism area. This research uses quantitative research methods with research locations in North Sumatra. Gradual sampling technique (multi-step random sampling). The sample size was determined as many as 60 HPI members from a total population of 114 HPI members. Data collection techniques used questionnaires, observing HPI members' social media and discussions with HPI management. Data analysis was carried out using descriptive statistics and inferential statistics in the form of a regression test.The results of the study show that in general HPI members access Facebook, WhatsApp, Youtube and Instagram social media. Apart from social media, another medium used by HPI in promoting Lake Toba tourism is using group communication. Regression analysis shows that there is an influence of social media activity on tourism promotion in the Lake Toba area.